Healthcare-seeking pattern in Sleman District, Yogyakarta: an observational analysis using secondary data of longitudinal surveillance system HDSS-Sleman cycle 2 (2016) - Razan Madyasta Athayanandi Wibowo (Berita Kedokteran Masyarakat (BKM), 2018)
ABSTRACTObjective Several factors that already persist in the society, namely person´s socioeconomic status (SES), beliefs and illness severity perception might play an important role for healthcare-seeking decision. This paper aims to investigate and describe the care-seeking behaviour pattern upon Sleman District´s population.Methods Secondary data derived from standardised interview and questionnaire were analysed. Each head of the household was asked regarding their family sociodemographic background, health status, and care-seeking behaviour pattern. The interview was belong to the second survey wave, gathered in amount of 19,593 participants, and were taking place between July and September 2015. Cut-off method was used to screen eligible participants, in which 11,516 remain. Bivariate analysis was done using Pearson-chi square method in order to observe the goodness of fit of population’s care-seeking pattern with sociodemographic variables and health status. Multivariate analysis was run through the logistic regression in order to predict and explain the relationship between care-seeking pattern and sociodemographic variables. Results In Sleman District, Yogyakarta, Indonesia –based on HDSS-Sleman second wave´s survey analysis, about four out of ten samples who stated themselves as sick in 2015 did still not practice care-seeking behaviour. Several demographic factors such sex, age, educational backgrounds, family wealth and health insurance ownership are significantly related with the care-seeking decision. But there was no significant care-seeking difference against parental ethnicity, as well as in District’s rural and urban area.Conclusions It has been confirmed that care-seeking behaviour upon Sleman District’s population depends on the person’s socioeconomic status and illness severity. Some important findings were including U-shaped function of care-seeking behaviour against some age groups and educational background.Keywords HDSS-Sleman, healthcare-seeking behaviour, Pearson-chi square, socioeconomic status (SES)